2006
DOI: 10.1371/journal.pgen.0020035
|View full text |Cite|
|
Sign up to set email alerts
|

Telomere Length as a Quantitative Trait: Genome-Wide Survey and Genetic Mapping of Telomere Length-Control Genes in Yeast

Abstract: Telomere length-variation in deletion strains of Saccharomyces cerevisiae was used to identify genes and pathways that regulate telomere length. We found 72 genes that when deleted confer short telomeres, and 80 genes that confer long telomeres relative to those of wild-type yeast. Among identified genes, 88 have not been previously implicated in telomere length control. Genes that regulate telomere length span a variety of functions that can be broadly separated into telomerase-dependent and telomerase-indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
209
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(230 citation statements)
references
References 42 publications
(50 reference statements)
18
209
0
Order By: Relevance
“…The average telomere length for the deletion mutants was calculated relative to wild-type length, and was grouped into the following categories: slightly short (< 50 bp shorter than wild type, SS); short (50-150 bp, S); very short (> 150 bp, VS); slightly long (< 50 bp longer than wild type, SL); long (50-150 bp, L); and very long (> 150 bp, VL) (Supplementary information, Table S1). Surprisingly, a great majority of the 168 mutants exhibited longer than normal telomeres (151 longer versus 17 shorter), which is the opposite of what has been reported in S. cerevisiae [4,5]. It remains unclear whether this represents a characteristic of telomere regulation in S. pombe.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…The average telomere length for the deletion mutants was calculated relative to wild-type length, and was grouped into the following categories: slightly short (< 50 bp shorter than wild type, SS); short (50-150 bp, S); very short (> 150 bp, VS); slightly long (< 50 bp longer than wild type, SL); long (50-150 bp, L); and very long (> 150 bp, VL) (Supplementary information, Table S1). Surprisingly, a great majority of the 168 mutants exhibited longer than normal telomeres (151 longer versus 17 shorter), which is the opposite of what has been reported in S. cerevisiae [4,5]. It remains unclear whether this represents a characteristic of telomere regulation in S. pombe.…”
mentioning
confidence: 77%
“…gene deletion, has become possible, and genome-wide phenotypic screening for gene function has been widely carried out. For example, Askree et al and Gatbonton et al examined the telomere-length change in about 4 800 non-essential gene deletion mutants of S. cerevisiae, and found that about 250 genes are involved in telomere-length regulation [4,5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The sequence of telomere repeats, abbreviated C 1-3 A/ TG [1][2][3] , of the related Saccharomyces sensu stricto species are completely conserved. However, the lengths of the telomere repeats vary greatly even among different strains within the same species [1,2].…”
Section: Dear Editormentioning
confidence: 99%
“…However, the lengths of the telomere repeats vary greatly even among different strains within the same species [1,2]. The sequences adjacent to the repeats are also rapidly evolving both within and among Saccharomyces species [3].…”
Section: Dear Editormentioning
confidence: 99%